International encyclopedia of the social sciences - Darity, William A. (Macmillan Reference USA, 2008)
Covers scholarship and fields that have emerged and matured since the publication of the original international edition. Highlights the expanding influence of economics in social science research and features new articles and biographies contributed by scholars from around the world on a wide array of global topics in the social sciences.